Plastic Surgery Techniques for the Improvement of Outcomes of Complex Obstetric Fistula Repairs - Pope, Rachel; Stokes, Mary; Brown, Roger H.; Chalamanda, Chisomo; Hollier, Larry H.; Wilkinson, Jeffrey P. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: As part of a larger study on the outcomes of obstetric fistula surgery, a review on patient outcomes when using gracilis muscle and/or Singapore flaps was conducted. Methods: The database queried includes over 1700 patients. Fifty-six cases were identified having had either a gracilis muscle and or a Singapore flap as part of the repair. Results: Twenty-one patients had a Singapore flap only. Median age was 26 years (19-55), four had one prior repair and two had two prior repair attempts. Nine cases were Goh type 3 and nine were Goh type 4 indicating urethral involvement. 71% (n=15) were >3 centimeters in diameter. Median estimated blood loss (ebl) was 200 ml and average OR time was 2.5 hours. Median catheter duration 17 days (13-25). 81% (n=17) were dye test negative, with an average pad weight of 19.2 grams. 19 patients had a gracilis muscle flap alone with median age of 43 (23-70). Four had one previous repair, one had four previous repairs. Nine were Goh type 3 and eight were Goh type 4. 70% (n=12) had a fistula >3 cm in diameter and 88% (n=15) had type iii considerations (previous repair attempt, circumferential, or severe scarring). Median ebl was 250 ml and average operative time was two hours and 30 minutes. Median catheter duration was 17 days (14-31). 82% (n=14) had negative dye tests, with average pad weight of 19 grams. 16 patients had both a Singapore and a gracilis. Median age was 31 (15-70), nine were Goh type 3, seven were Goh type 4. 87.5% (n=14) had a fistula that was more than 3 cm in diameter and 87.5% (n=14) were type iii. Median ebl was 300 ml (250-1000 ml), and average operative time was 3 hours and 45 minutes. 81% (n=13) had a negative dye test, with two patients going home positive and returning negative over the course of four months. Average pad weight was 18.9 grams. Conclusions: For large fistulas with a significant amount of vaginal tissue loss, the Singapore flap is a potential option for improved outcomes. For recurrent cases and those with poor quality tissue, the gracilis muscle may lead to overall improved outcomes. Overall, these techniques are useful for complex obstetric fistula cases where outcomes are generally less favorable. Further prospective studies are needed.